Development of Solid Elasticity Modules with Guided Inquiry Model to Train Critical Thinking Skills - Mena Yani; Mastuang Mastuang; Misbah Misbah (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2021)
Currently, few physics modules train critical thinking skills on the elasticity of solids. Therefore, a solid elasticity module was developed with a guided inquiry model to improve students' critical thinking skills. This research aims to produce a valid, practical, and effective learning module so that it is suitable for use in training students' critical thinking skills. This research is research & development with a design of the Dick and Carrey model. The subject of the pilot study was class XI IPA with 31 students in one of the public high schools in the city of Banjarmasin. The learning outcomes modules and tests developed were validated by 2 (two) academic validators and 1 (one) practitioner through a validation sheet. The practicality of this module is measured through the implementation of the Lesson Plan (RPP) by 3 (three) observers. The effectiveness of this module is measured using a learning outcome test that includes critical thinking skills, which are then analyzed using the N-gain equation. The results showed that: 1) the validity of the module obtained a score of 3.7, which was categorized as very valid, 2) the practicality of the module based on the lesson plan implementation sheet obtained a score of 3.5, which was categorized as very practical, 3) the effectiveness of the module based on the results of the learning test obtained an n-gain score of 0.66 with medium category critical thinking skills. It is concluded that the module of the solidity elasticity of the guided inquiry model is feasible to train students' critical thinking skills.